(untitled) - Majda, Viliam (Doprava a spoje, 2007)
A changes in the Slovak legislation brought univocally responsibility of a cities and a self-governement regions for the public transport from January 1st 2005. These changes removed an inconsistency and a lack of system issued from a recent reality.